The Effect of Price and Climatic Variables on Maize Supply in Ghana - Acquah, Henry De-Graft (Journal of Social and Development Sciences, 2013)
This study examines the effect of previous price and climatic variables on maize supply in Ghana. For this purpose, two separate approaches are used: (i) a lag model using the OLS technique and (ii) a quantile regression approach. Results from the lag model indicates that an increase in previous year maize price and previous growing season temperature positively affect current year maize supply. However, an increase in previous growing season rainfall negatively affects current year maize supply. The quantile regression results show that maize supply responds differently to previous maize price and climatic variables across the different quantiles of crop area distribution.